Work Environment and Elderly Abuse in Nursing Homes: The Mediating Role of Burnout. Issue 11 (June 2021) - Andela, Marie; Truchot, Didier; Huguenotte, Virginie
The present study focuses on elderly abuse committed by nurses and nurses' aides in nursing homes. Elderly abuse includes neglect and abusive behaviors deleterious to the health and welfare of the elderly. The study aimed at a better understanding of neglect and abusive behaviors by considering caregiver burnout and the work context of these professionals. To achieve this goal, direct effects of job demands (workload and emotional demands) and organizational resources (quality of relationships with colleagues and with the supervisor) on elderly abuse were analyzed. Moreover, the mediating role of caregiver burnout was explored by suggesting that job demands and lack of organizational resources were related to neglect and abusive behaviors through burnout. The study was conducted among 481 nurses and health care assistants from different French nursing homes. Correlations, multiple regressions, and mediation analyses were performed. Results globally confirmed our hypotheses. Emotional demands and poor quality relationships with colleagues and the team supervisor were the most predictive variables for caregiver burnout, neglect, and abusive behaviors toward the elderly. Moreover, the results contributed to the literature by highlighting the mediating effect of burnout and give rise to potential implications in preventing elderly abuse in nursing homes.